2021
DOI: 10.1111/iej.13573
|View full text |Cite
|
Sign up to set email alerts
|

Trial registration and selective outcome reporting in Endodontic Research: Evidence over a 5‐year period

Abstract: Aim To assess the prevalence of registration of clinical trials in endodontic research and to identify outcome reporting discrepancies between trial registration entries and respective final publications. Associations with publication characteristics, such as journal, year of publication, origin, number of centres and authors, funding and statistical significance of the findings, were also sought. Methodology All reports of endodontic randomized controlled trials (RCTs) published in 4 endodontic specialty and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Among oral health published RCTs, we found that almost half had primary outcomes differing from that registered (44.9%). This rate is consistent with SOR rates in endodontics (36.4%) (Tzanetakis and Koletsi 2021), implantology (55%) (Sendyk et al 2019), and orthodontics (47%) (Koufatzidou et al 2019). Similar SOR rates were found in medicine (Dwan et al 2011) and when authors compared systematic reviews to protocols (45.4%) (Pandis et al 2015).…”
Section: Sorsupporting
confidence: 84%
See 1 more Smart Citation
“…Among oral health published RCTs, we found that almost half had primary outcomes differing from that registered (44.9%). This rate is consistent with SOR rates in endodontics (36.4%) (Tzanetakis and Koletsi 2021), implantology (55%) (Sendyk et al 2019), and orthodontics (47%) (Koufatzidou et al 2019). Similar SOR rates were found in medicine (Dwan et al 2011) and when authors compared systematic reviews to protocols (45.4%) (Pandis et al 2015).…”
Section: Sorsupporting
confidence: 84%
“…In a previous study, we found that only 23% of a sample of 317 RCTs with results published in oral health journals were registered in a public register, and among those, 91% were registered retrospectively (Smaïl-Faugeron et al 2015). Moreover, studies in specific dental areas such as endodontics, orthodontics, and implantology found high rates of SOR (Koufatzidou et al 2019; Sendyk et al 2019; Tzanetakis and Koletsi 2021). These results suggest that the risk of reporting bias is high in the field of oral health in general.…”
Section: Introductionmentioning
confidence: 99%
“…Most severely impacted domains were registration, publication bias reporting, reporting of summary measures, and planned analyses ( 15 ). Indeed, a variety of methodological and reporting flaws in these domains have been convulsing relevant research in Oral Health and specialties other than Orthodontics as well ( 17–19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings, the study of Makou et al (2021) identified study design‐oriented spin , with observational type SRs being mostly affected, whilst again a trend was observed for non‐significant meta‐analyses to be less affected by this flaw (Makou et al, 2021). The former effect has been demonstrated in other types of methodological flaws of original studies as well because observational and non‐randomized studies have been considered of lower quality overall in terms of evidence perspectives (Gratsia et al, 2019; Koletsi et al, 2015; Tzanetakis & Koletsi, 2021b, 2021c). Regarding the latter, one might consider this is related to the overall nature of the identified spin domains, with authors of most SRs being more prone to overstress the conceivably significant findings, disregarding the limitations of the contributing primary studies or overstating a statistically significant p ‐value result (Koletsi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this report, international collaborations as well as trial registration accounted for improved reporting and interpretation, contrary to spin practices. The latter has also been acknowledged universally as a backbone practice for providing transparency and credibility in disseminated research findings (Fleming et al, 2015; Koufatzidou et al, 2019; Tzanetakis & Koletsi, 2021b, 2021c). Similarly, abstracts of RCTs in periodontology and implantology have been reported to present spin in almost 70% of their reports (Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%